Mesoporous biochar derived from Egyptian doum palm (Hyphaene thebaica) shells as low-cost and biodegradable adsorbent for the removal of methyl orange dye: Characterization, kinetic and adsorption mechanism - Constant Tcheka; Marrigje Marianne Conradie; Vagai Alahamdi Assinale; Jeanet Conradie (Chemical Physics Impact, 2024)
The present research work reports the preparation of Hyphaene thebaica derived-biochar (HTBC) and its applicability as eco-friendly and low-cost adsorbent for the removal of methyl orange (MO) dye. The main physicochemical characteristics of HTBC including its morphology, crystallinity and chemical function groups were determined through scanning electron microscopy (SEM), energy dispersion spectroscopy (EDS), powder X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). The results showed that HTBC adsorbent was found to be constituted by heterogeneous surface with mesoporous having a surface area of 33.38 m2/g and pore diameter of 23.53 nm, and carboxylic and amine functional groups. Adsorption experiments were conducted using batch mode, by varying key adsorption parameters such as contact time, solution pH, adsorbent dosage and concentration. Adsorption isotherm modelling revealed that the Langmuir model (higher R2 and lower χ2) provided a better fit for MO adsorption onto HTBC, while the adsorption kinetics followed a pseudo-second-order kinetic model. Under optimized conditions (pH 2, HTBC dose of 0.03 g, initial dye concentration of 100 mg/L, 313 K, 270 rpm), the maximum Langmuir monolayer adsorption capacity for MO adsorption onto HTBC was found to be 264.922 mg/g. According the thermodynamic parameters, it can be deduced that MO adsorption on HTBC was exothermic and spontaneous. Adsorption mechanism can be attributed to various interactions, including electrostatic attraction, H-bonding, and π-π interaction. In light of these findings, biochar from Hyphaene thebaica shells can be considered a cost-effective and biodegradable adsorbent with significant potential for the treatment of water contaminated with anionic dyes.